Coal - An Evaluation of the Performance of Thirty-three Residential Stoker Coals - James B. Purdy; Harlan W. Nelson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1950)
The great majority of stokers used in residential heating installations are of the clinkering type. Because of inherent characteristics of the underfeed combustion process as it occurs in these small stokers, and because of the wide range of operating conditions encountered in residential heating schedules, not all bituminous coals can be used successfully in residential underfeed units. The problem of providing consumer satisfaction has been attacked by the joint efforts of the stoker manufacturers and the coal industry; the stoker manufacturers have been concerned with improving their product to permit the use of a wider range of coals, and coal operators have made every effort to market selected and better prepared coals. In view of the wide range of physical characteristics and chemical properties of bituminous coals, the problems are real and are receiving increased attention. Some twelve years ago a laboratory method was developed at Battelle Memorial Institute for the relative evaluation of coals for use in residential underfeed stokers. The method was developed in conjunction with work being done at that time for Bituminous Coal Research, Inc., and for individual coal producers, to obtain information on the characteristics of coal that determined the successful performance of the small stoker. Details of the equipment and test procedure were given by R. A. Sherman1 in a paper presented at the University of Illinois Fifth Short Course in Coal Utilization. During the past several years, the evaluation of over forty different coals has been determined by investigations sponsored at Battelle by coal operators in the eastern producing districts. The purpose of this paper is to compare the results and conclusions derived from the various tests with marketing experiences of the operators, and to discuss briefly the relationship of test results to standard laboratory determinations. Equipment Used in Tests Fig 1 shows schematically the equipment used in the evaluation tests. The stoker is a commercial model of conventional design, having a nominal feed rate of 30 Ib per hr. A special laboratory furnace is used, which is tightly sealed to prevent the entrance of secondary air. The complete stoker-furnace assembly is mounted on platform scales which permits the measurement of combustible weight losses occurring during the test. The furnace stack, in which are a thermocouple, flue-gas sampling tube, and smoke meter, is connected to the laboratory exhaust breeching through a friction-less connection. Through use of an auxiliary blower system, provision is made for the measurement of the air delivered by the stoker fan to the windbox. A water seal in the duct work eliminates inter-